High-compaction ferric sodium pyrophosphate positive electrode material and preparation method thereof

By doping titanium, vanadium, and zirconium elements and combining secondary sanding and secondary sintering processes, high-pressure sodium iron pyrophosphate positive electrode material is prepared, which solves the problem of low compaction density, improves the compaction density and electrochemical performance of the material, and is suitable for sodium ion batteries.

CN120348921AActive Publication Date: 2025-07-22ANHUI XINNA MATERIAL SCIENCE & TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510844316.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-07-22
Estimated Expiration
2045-06-23

AI Technical Summary

Technical Problem

The compaction density of existing sodium ferric phosphate cathode materials is low, which limits the volume energy density and industrial application of sodium ion batteries.

Method used

The high-pressure sodium iron phosphate pyrophosphate positive electrode material is prepared by doping titanium, vanadium and zirconium elements, combined with secondary sand grinding and secondary sintering processes, and the compaction density and electrochemical activity of the material are improved by controlling the particle size and morphology.

Benefits of technology

It significantly improves the compaction density and electrochemical performance of sodium iron pyrophosphate cathode material, achieves high capacity and good rate performance, and is suitable for large-scale energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120348921A_ABST
    Figure CN120348921A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and discloses a high-compaction ferric sodium pyrophosphate positive electrode material and a preparation method thereof.The chemical formula of the positive electrode material is Na4Fe2.9VxTiyZrz (PO4) 2P2O7, 0.001 < = x < = 0.01, 0.002 < = y < = 0.01, and 0.001 < = z < = 0.01. The preparation method comprises the following steps that a sodium source, an iron source, a phosphorus source, a carbon source, a vanadium source, a titanium source and a zirconium source are weighed and mixed to be uniform, and a mixture is obtained; carrying out primary sanding treatment to obtain first sanding slurry, carrying out spray drying, and carrying out primary sintering treatment to obtain a pre-sintered material; adding a proper amount of carbon source into the pre-sintered material, and carrying out secondary sanding treatment to obtain a second ground material; and carrying out spray drying on the second grinding material, and carrying out secondary sintering treatment to obtain the positive electrode material. The high-compaction ferric sodium pyrophosphate positive electrode material provided by the invention has high compaction density and excellent rate capability and cycle performance, and can be used for preparing a sodium ion battery with high compaction density, high capacity and good rate capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of positive electrode materials for sodium ion batteries, and in particular to a high-density sodium iron pyrophosphate positive electrode material and a preparation method thereof. Background Art

[0002] Sodium iron pyrophosphate is one of the three main materials for sodium ion positive electrode materials. It has a theoretical specific capacity of 120mAh / g and has the advantages of high working voltage, high safety, long cycle life and good low temperature performance. It is used in the field of large-scale energy storage. However, the compaction density of sodium iron pyrophosphate materials has always been low. The powder compaction density of the currently industrialized sodium iron pyrophosphate materials is generally 1.9~2.0g / cm 3 For sodium-ion batteries, the greater the compaction density of the cathode material powder, the higher the volume energy density of the battery can be, and the more competitive the product will be.

[0003] The patent application with publication number CN119637395A discloses a production line and method for high-density sodium-ion battery positive electrode materials, including a primary sintering unit and a secondary sintering unit. By combining equipment layout with process, a production line and production method are provided that can realize continuous large-scale production of high-density sodium-ion battery positive electrode materials. On the one hand, the yield rate can be improved and the production capacity can be increased; on the other hand, two or more different particle sizes can be produced simultaneously, and the particle size grading can be completed to obtain high-density sodium-ion battery positive electrode materials.

[0004] However, there are still many technical routes to choose from for high-pressure compacted sodium iron pyrophosphate positive electrode materials, and the process stability needs to be improved, and large-scale production and widespread application of high-pressure compacted sodium iron pyrophosphate positive electrode materials cannot be achieved. Summary of the invention

[0005] In view of the deficiencies in the prior art, one of the objectives of the present invention is to provide a high-density sodium iron pyrophosphate positive electrode material and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A high-density sodium iron pyrophosphate positive electrode material, the chemical formula of the positive electrode material is: Na4Fe 2.9 V x Ti y Zr z (PO4)2P2O7, wherein 0.001≤x≤0.01, 0.002≤y≤0.01, 0.001≤z≤0.01.

[0007] The preparation method of the high-pressure compacted sodium iron pyrophosphate positive electrode material comprises the following steps: Step (1): Add sodium source, iron source, phosphorus source, carbon source, vanadium source, titanium source and zirconium source into solvent water and disperse evenly to obtain a slurry. Step (2): Place the well-mixed slurry in a sand mill and conduct primary sand milling to obtain a first abrasive. Step (3): Transfer the first abrasive into a spray dryer and conduct spray granulation to obtain a precursor powder. Step (4): Conduct primary sintering treatment on the precursor powder to obtain a pre-sintered material. Step (5): Add a carbon source to the pre-sintered material and conduct secondary sand milling to obtain a second abrasive. Step (6): After spray drying the second abrasive, conduct secondary sintering treatment to obtain a cathode material.

[0008] Preferably, in step (1), the iron source is lamellar iron phosphate, and the lamellar thickness of the lamellar iron phosphate < 200 nm; the particle size D50 of the lamellar iron phosphate < 15 μm.

[0009] The pores between the lamellar structures ensure more sufficient contact between the doping elements and iron phosphate grains during the sintering process. At the same time, due to the relatively thin lamellar thickness, it is beneficial for the diffusion of doping element ions during the high-temperature sintering process, so as to fully ensure the doping effect.

[0010] Preferably, in step (1), the sodium source is one or more of sodium carbonate, sodium oxalate, sodium pyrophosphate, sodium dihydrogen pyrophosphate, sodium dihydrogen phosphate and disodium hydrogen phosphate; Preferably, the phosphorus source is one or more of sodium pyrophosphate, sodium dihydrogen pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; Preferably, the carbon source is one or more of glucose, sucrose, citric acid, ascorbic acid, polyethylene glycol; Preferably, the vanadium source is one or more of vanadium carbonate, vanadium pentoxide, ammonium metavanadate; Preferably, the titanium source is one or more of titanium dioxide, tetrabutyl titanate, tetraisopropyl titanate; Preferably, the zirconium source is one or more of sodium zirconate, zirconium dioxide, zirconium hydroxide.

[0011] Preferably, in step (1), the molar ratio of sodium, iron, and phosphorus elements is 4:2.9:4, and the carbon source accounts for 6%-10% of the total weight of the iron source; Preferably, the molar doping amounts of V, Ti, and Zr are: 0.001 ≤ x ≤ 0.01, 0.002 ≤ y ≤ 0.01, 0.001 ≤ z ≤ 0.01.

[0012] Preferably, in the step (2), the specific steps of the primary grinding treatment are as follows: placing the mixed slurry in a sand mill, using zirconia beads with a diameter of 0.3 - 0.5 mm, grinding for 4 h at a rotation speed of 800 rpm, and controlling the particle size distribution of the first abrasive to be D50 = 8 μm and D90 = 15 μm.

[0013] Preferably, in the step (3), the specific steps of spray granulation are as follows: transferring the first abrasive to a spray dryer, granulating under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain spherical precursor powder with a smooth surface and a particle size of 10 - 20 μm.

[0014] Preferably, in the step (4), the sintering regime of the primary sintering is as follows: heating from room temperature to 300 °C at a heating rate of 2 °C / min, holding for 3 h in an N2 atmosphere, then heating to 500 °C, and holding for 12 h in a 5 wt% H2 / N2 reducing atmosphere.

[0015] Preferably, in the step (5), the carbon source accounts for 4% - 8% of the total weight of the pre-sintered material; the sintering regime of the secondary sintering is as follows: heating from room temperature to 530 °C at a heating rate of 2 °C / min and holding for 10 h in an N2 atmosphere.

[0016] The second object of the present invention is to provide a sodium ion battery, including a positive electrode material, an electrolyte, a negative electrode material, and a separator, wherein the positive electrode material is the above-mentioned high-compaction sodium iron pyrophosphate positive electrode material.

[0017] Compared with the prior art, the advantages of the present invention are as follows: (1) The doping scheme adopted in the present invention can improve the compaction density and electrochemical activity of sodium iron pyrophosphate: the doping of titanium element can improve the compaction density of the material, and after introducing vanadium and zirconium elements, the doped vanadium and zirconium atoms can form a three-dimensional diffusion channel for sodium ions in the sodium iron pyrophosphate structure, realizing the improvement of capacity and rate performance.

[0018] (2) The secondary grinding process adopted in the present invention, through precise control of grinding parameters, combines small particle size grinding beads with low rotation speed to achieve the directional cleavage and fragmentation of lamellar iron phosphate, control the particle size while retaining the lamellar structure, ensure the formation of anisotropically stacked spherical nuclei during spray drying, and the tap density is increased by 15% compared with traditional particles; the spherical precursor can reduce grain boundary defects during subsequent sintering, and the smooth surface reduces the interfacial resistance during carbon coating.

[0019] (3) The secondary sintering process adopted in the present invention can achieve uniform coating of the carbon source and effectively improve the conductivity of the material. First, the carbon source is pre-coated on the flaky precursor, which can improve the effect of the first carbon coating. After the first sintering, secondary sanding is carried out for the second coating, so as to improve the uniformity of the carbon coating of the overall structure, overcome the defects caused by the morphological differences, and is beneficial to improving the uniformity of the carbon coating of the overall material, thereby obtaining better electrical conductivity.

[0020] (4) The chemical ratios of sodium, iron, and phosphorus elements in the raw materials used in the present invention are easy to control by batching, and the raw materials are simple and easy to obtain; the process used in the present invention is simple, the process is reliable, the manufacturing process is fast, and it is easy to carry out large-scale production and wide application.

[0021] (5) The XRD test results show that the sodium iron pyrophosphate phosphate prepared by this method is a typical orthorhombic system, space group Pn21a. In the voltage range of 2-4 V, the discharge specific capacity at 0.1 C can be as high as 102 mAh / g. After 50 charge-discharge cycles at a 1 C rate, the discharge specific capacity still remains at 90 mAh / g, and the Coulomb efficiency is stable at 99.9%. Its excellent cycle stability enables it to be applied in the field of large-scale energy storage. Brief Description of the Drawings

[0022] Figure 1 It is the scanning electron microscope image of the flaky iron phosphate used in the present invention.

[0023] Figure 2 It is the scanning electron microscope image of the sodium iron pyrophosphate phosphate prepared in Example 1 of the present invention.

[0024] Figure 3 It is the XRD pattern of the sodium iron pyrophosphate phosphate prepared in Example 1 of the present invention.

[0025] Figure 4 It is the rate charge-discharge curve graph of the sodium ion battery prepared in Example 1 of the present invention.

[0026] Figure 5 It is the cycle curve graph of the sodium ion battery prepared in Example 1 of the present invention at a 1 C rate. Detailed Description of the Invention

[0027] The following further describes in detail a high-compact sodium iron pyrophosphate phosphate cathode material and a preparation method thereof in combination with specific embodiments. These embodiments are only for the purpose of comparison and explanation, and the present invention is not limited to these embodiments. Example 1

[0028] A preparation method of a high-compact sodium iron pyrophosphate phosphate cathode material includes the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, glucose accounting for 7.5% of the total weight of iron phosphate, 0.0015 mol of ammonium metavanadate, 0.003 mol of tetrabutyl titanate, and 0.0015 mol of zirconium carbonate, and add them to deionized water in sequence for dispersion.

[0029] (2) Place the mixed slurry in a sand mill for primary sanding treatment, that is, use zirconia beads with a diameter of 0.5 mm and sand at a speed of 800 rpm for 4 h. Control the particle size distribution of the first abrasive: D50 = 8 μm, D90 = 15 μm to obtain the first abrasive. Transfer the first abrasive to a spray dryer and granulate it under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain the precursor powder.

[0030] (3) Conduct primary sintering treatment on the precursor powder, that is, heat from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat to 500 °C and hold for 12 h to obtain the pre-sintered material.

[0031] (4) Add polyethylene glycol accounting for 8% of the total weight of the pre-sintered material to the pre-sintered material for secondary sanding treatment to obtain the second abrasive; transfer the second abrasive to a spray dryer for spray granulation.

[0032] (5) Conduct secondary sintering treatment on the second abrasive after spray granulation, that is, heat from room temperature to 530 °C at a sintering heating rate of 2 °C / min and hold for 10 h, and hold for 10 h in an N2 atmosphere to obtain the positive electrode material. Example 2

[0033] A preparation method of a high-compact sodium iron pyrophosphate positive electrode material, comprising the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, glucose accounting for 7.5% of the total weight of iron phosphate, 0.001 mol of ammonium metavanadate, 0.002 mol of tetrabutyl titanate, and 0.001 mol of zirconium carbonate, and add them to deionized water in sequence for dispersion.

[0034] (2) Place the mixed slurry in a sand mill for primary sanding treatment, that is, use zirconia beads with a diameter of 0.3 mm and sand at a speed of 800 rpm for 4 h. Control the particle size distribution of the first abrasive: D50 = 8 μm, D90 = 15 μm to obtain the first abrasive. Transfer the first abrasive to a spray dryer and granulate it under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain the precursor powder.

[0035] (3) Subject the precursor powder to a primary sintering treatment, that is, heat from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat to 500 °C and hold for 12 h to obtain a pre-sintered material.

[0036] (4) Add polyethylene glycol accounting for 8% of the total weight of the pre-sintered material to the pre-sintered material for a secondary sanding treatment to obtain a second abrasive; transfer the second abrasive to a spray dryer for spray granulation.

[0037] (5) Subject the second abrasive after spray granulation to a secondary sintering treatment, that is, heat from room temperature to 530 °C at a sintering heating rate of 2 °C / min and hold for 10 h, and hold for 10 h in an N2 atmosphere to obtain the cathode material. Example 3

[0038] A method for preparing a high-compactness sodium iron pyrophosphate phosphate cathode material, comprising the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, glucose accounting for 7.5% of the total weight of iron phosphate, 0.002 mol of ammonium metavanadate, 0.004 mol of tetrabutyl titanate, and 0.002 mol of zirconium carbonate, and add them to deionized water in sequence for dispersion.

[0039] (2) Place the mixed slurry in a sand mill for a primary sanding treatment, that is, use zirconia beads with a diameter of 0.5 mm to sand for 4 h at a rotation speed of 800 rpm, control the particle size distribution of the first abrasive D50 = 8 μm, D90 = 15 μm to obtain the first abrasive, transfer the first abrasive to a spray dryer, and granulate under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain a precursor powder.

[0040] (3) Subject the precursor powder to a primary sintering treatment, that is, heat from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat to 500 °C and hold for 12 h to obtain a pre-sintered material.

[0041] (4) Add polyethylene glycol accounting for 8% of the total weight of the pre-sintered material to the pre-sintered material for a secondary sanding treatment to obtain a second abrasive; transfer the second abrasive to a spray dryer for spray granulation.

[0042] (5) Subject the second abrasive after spray granulation to a secondary sintering treatment, that is, heat from room temperature to 530 °C at a sintering heating rate of 2 °C / min and hold for 10 h, and hold for 10 h in an N2 atmosphere to obtain the cathode material. Example 4

[0043] A method for preparing a high-compactness sodium iron pyrophosphate phosphate cathode material, comprising the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, glucose accounting for 10% of the total weight of iron phosphate, 0.0015 mol of ammonium metavanadate, 0.003 mol of tetrabutyl titanate, and 0.0015 mol of zirconium carbonate, and add them to deionized water in sequence for dispersion.

[0044] (2) Place the mixed slurry in a sand mill for primary sanding treatment, that is, use zirconia beads with a diameter of 0.3 mm and sand at a speed of 800 rpm for 4 h. Control the particle size distribution of the first abrasive: D50 = 8 μm, D90 = 15 μm to obtain the first abrasive. Transfer the first abrasive to a spray dryer and granulate it under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain the precursor powder.

[0045] (3) Conduct primary sintering treatment on the precursor powder, that is, heat it from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat it to 500 °C and hold for 12 h to obtain the pre-sintered material.

[0046] (4) Add polyethylene glycol accounting for 4% of the total weight of the pre-sintered material to the pre-sintered material for secondary sanding treatment to obtain the second abrasive; transfer the second abrasive to a spray dryer for spray granulation.

[0047] (5) Conduct secondary sintering treatment on the second abrasive after spray granulation, that is, heat it from room temperature to 530 °C at a sintering heating rate of 2 °C / min and hold for 10 h, and hold for 10 h in an N2 atmosphere to obtain the cathode material. Example Five

[0048] A preparation method of a high-compact sodium iron pyrophosphate cathode material includes the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, glucose accounting for 6% of the total weight of iron phosphate, 0.0015 mol of ammonium metavanadate, 0.003 mol of tetrabutyl titanate, and 0.0015 mol of zirconium carbonate, and add them to deionized water in sequence for dispersion.

[0049] (2) Place the mixed slurry in a sand mill for primary sanding treatment, that is, use zirconia beads with a diameter of 0.5 mm and sand at a speed of 800 rpm for 4 h. Control the particle size distribution of the first abrasive: D50 = 8 μm, D90 = 15 μm to obtain the first abrasive. Transfer the first abrasive to a spray dryer and granulate it under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain the precursor powder.

[0050] (3) Perform a primary sintering treatment on the precursor powder, that is, heat from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat to 500 °C and hold for 12 h to obtain a pre-sintered material.

[0051] (4) Add polyethylene glycol accounting for 8% of the total weight of the pre-sintered material to the pre-sintered material for a secondary sanding treatment to obtain a second abrasive; transfer the second abrasive to a spray dryer for spray granulation.

[0052] (5) Perform a secondary sintering treatment on the second abrasive after spray granulation, that is, heat from room temperature to 530 °C at a sintering heating rate of 2 °C / min and hold for 10 h, and hold for 10 h in an N2 atmosphere to obtain a cathode material.

[0053] Comparative Example 1 A preparation method of a high-compact sodium iron pyrophosphate cathode material includes the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, and 7.5% of glucose based on the total weight of iron phosphate, and add them to deionized water in sequence for dispersion.

[0054] (2) Place the mixed slurry in a sand mill for a primary sanding treatment, that is, use zirconia beads with a diameter of 0.5 mm to sand for 4 h at a rotation speed of 800 rpm, control the particle size distribution of the first abrasive D50 = 8 μm, D90 = 15 μm to obtain the first abrasive, transfer the first abrasive to a spray dryer, and granulate under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain a precursor powder.

[0055] (3) Perform a primary sintering treatment on the precursor powder, that is, heat from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat to 500 °C and hold for 12 h to obtain a pre-sintered material.

[0056] (4) Add polyethylene glycol accounting for 8% of the total weight of the pre-sintered material to the pre-sintered material for a secondary sanding treatment to obtain a second abrasive; transfer the second abrasive to a spray dryer for spray granulation.

[0057] (5) Perform a secondary sintering treatment on the second abrasive after spray granulation, that is, heat from room temperature to 530 °C at a sintering heating rate of 2 °C / min and hold for 10 h, and hold for 10 h in an N2 atmosphere to obtain a cathode material.

[0058] Comparative Example 2 A preparation method of a high-compact sodium iron pyrophosphate cathode material includes the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, 7.5% of the total weight of iron phosphate of glucose, 0.01 mol of ammonium metavanadate, 0.01 mol of tetrabutyl titanate, and 0.01 mol of zirconium carbonate, and add them to deionized water in sequence for dispersion.

[0059] (2) Place the mixed slurry in a sand mill for a primary sanding treatment, that is, use zirconia beads with a diameter of 0.5 mm, sand at a rotational speed of 800 rpm for 4 h, control the particle size distribution of the first abrasive D50 = 8 μm, D90 = 15 μm to obtain the first abrasive, transfer the first abrasive to a spray dryer, and granulate under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain the precursor powder.

[0060] (3) Perform a primary sintering treatment on the precursor powder, that is, heat from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat to 500 °C and hold for 12 h to obtain the pre-sintered material.

[0061] (4) Add polyethylene glycol accounting for 8% of the total weight of the pre-sintered material to the pre-sintered material for a secondary sanding treatment to obtain the second abrasive; transfer the second abrasive to a spray dryer for spray granulation.

[0062] (5) Perform a secondary sintering treatment on the second abrasive after spray granulation, that is, heat from room temperature to 530 °C at a sintering heating rate of 2 °C / min and hold for 10 h, and hold for 10 h in an N2 atmosphere to obtain the cathode material.

[0063] Comparative Example 3 A preparation method of a high-compact sodium iron pyrophosphate cathode material includes the following steps: (1) Weigh 1.45 mol of sodium oxalate, 2.9 mol of iron phosphate, 1.1 mol of sodium dihydrogen phosphate, 7.5% of the total weight of iron phosphate of glucose, 8% of the total weight of iron phosphate of polyethylene glycol, 0.01 mol of ammonium metavanadate, 0.01 mol of tetrabutyl titanate, and 0.01 mol of zirconium carbonate, and add them to deionized water in sequence for dispersion.

[0064] (2) Place the mixed slurry in a sand mill for sanding treatment, that is, use zirconia beads with a diameter of 0.5 mm, sand at a rotational speed of 800 rpm for 4 h, control the particle size distribution of the first abrasive D50 = 8 μm, D90 = 15 μm to obtain the first abrasive, transfer the first abrasive to a spray dryer, and granulate under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain the precursor powder.

[0065] (3) Sinter the precursor powder, that is, heat it from room temperature to 300 °C at a sintering heating rate of 2 °C / min and hold for 3 h, then heat it to 500 °C and hold for 12 h to obtain the cathode material.

[0066] Test: Use the sodium iron pyrophosphate prepared in Examples 1-5 and Comparative Examples 1-3 as the cathode active material for sodium-ion batteries. Mix it with the conductive agent SP and the binder PVDF according to a mass ratio of 90:5:5. The current collector is aluminum foil to form the cathode; use a sodium metal sheet as the anode of the sodium-ion electrode, use glass fiber as the separator, and use a 1 mol / L NaPF6 EC / DMC (volume ratio 1:1) + 5% FEC solution as the electrolyte. Assemble the battery in a glove box with an oxygen partial pressure less than 0.01 PPM, a water partial pressure less than 0.01 PPM, and an argon atmosphere. Use the constant current constant voltage charging - constant current discharging mode, with a voltage range of 2-4 V, and perform charge and discharge tests at current densities of 0.1 C - 0.2 C - 0.5 C - 1 C.

[0067] Use the sodium iron pyrophosphate prepared in Examples 1-5 and Comparative Examples 1-3 as the test sample for the compaction density meter. Use the Yuaneng Technology PCD2000 type compaction density meter to perform tests under a test pressure of 3T.

[0068] Table 1: Performance test data table of each example and comparative example

[0069] Table 1 shows the test results of eight groups of experiments. It can be seen from the test results of the compaction density meter that the material prepared by doping 1500 ppm of vanadium, 3000 ppm of titanium, and 1500 ppm of zirconium in every 1 mol of sodium iron pyrophosphate has a higher compaction density. In Example 2, the doping ratio of each element was reduced, and in Example 3, the doping ratio of each element was increased. The compaction density of the prepared materials is less than that of Example 1; in Comparative Example 1, no elements were doped, and in Comparative Example 2, an excessive amount of elements was doped. The compaction density of the prepared materials is significantly lower than that of Example 1. It shows that the element doping ratio in Example 1 is the most reasonable. In Example 4, the glucose ratio in the primary abrasive was increased, and in Example 5, the glucose ratio in the primary abrasive was reduced. The compaction density of the prepared materials is slightly less than that of Example 1. It shows that the carbon source pre-coating effect in Example 1 is the most reasonable. In Comparative Example 3, the secondary sintering process was not adopted, and the compaction density of the prepared materials is significantly lower than that of Example 1. It shows that the secondary sintering process adopted in Example 1 is more reasonable.

[0070] Figure 1SEM image of the layered iron phosphate used in the present invention. As can be seen from the figure, the morphology of the iron phosphate is a typical layered sheet structure, and the thickness of the sheets of the layered iron phosphate < 200 nm; the particle size D50 of the sheet-like iron phosphate < 15 μm.

[0071] Figure 2 SEM image of the sodium iron pyrophosphate prepared in Example 1 of the present invention. As can be seen from the figure, the particle morphology is spherical, the size of the sample particles is 2 - 20 μm, the particle surface is relatively smooth, and the carbon coating effect on the particle surface is good.

[0072] Figure 3 XRD pattern of the NFPP prepared in Example 1 of the present invention. The crystal structure of the material was analyzed by X-ray diffraction test. The results showed that diffraction peaks of the NFPP composite phase existed at 9.8º, 15.8º, 16.7º, 32.1º, and 33.6º, corresponding to the (200), (011), (210), (022), and (222) crystal planes of the material respectively. The XRD results proved that the material synthesized by this formulation process was the crystal phase of sodium iron pyrophosphate.

[0073] Figure 4 Rate charge-discharge curve of the sodium-ion battery prepared in Example 1 of the present invention. The sample can provide discharge specific capacities of 106.50 mAh / g, 105.01 mAh / g, 102.94 mAh / g, and 101.54 mAh / g at the rates of 0.1C, 0.2C, 0.5C, and 1C respectively, and the 1C capacity retention rate is 95.34%.

[0074] Figure 5 Cycle curve of the sodium-ion battery prepared in Example 1 of the present invention at a 1C rate. After 50 charge-discharge cycles at a 1C rate, the discharge specific capacity still maintained at 100.64 mAh / g, and the Coulomb efficiency was stable at 99.9%, indicating that the material had excellent cycle stability.

[0075] The present invention illustrates a high-compaction sodium iron pyrophosphate cathode material and its preparation method through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent substitution of each raw material of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high-compact sodium iron pyrophosphate phosphate cathode material, characterized in that, The chemical formula of the positive electrode material is expressed as: Na4Fe 2.9 V x Ti y Zr z (PO4)2P2O7, where 0.001 ≤ x ≤ 0.01, 0.002 ≤ y ≤ 0.01, 0.001 ≤ z ≤ 0.

01.

2. The high-compaction sodium iron pyrophosphate cathode material as described in claim 1, characterized in that, The preparation method of the high-compact sodium iron pyrophosphate cathode material comprises the following steps: Step (1): Add a sodium source, an iron source, a phosphorus source, a carbon source, a vanadium source, a titanium source, and a zirconium source into solvent water and disperse them evenly to obtain a slurry; Step (2): Place the mixed slurry in a sand mill and perform primary sanding treatment to obtain a first abrasive; Step (3): Transfer the first abrasive into a spray dryer and perform spray granulation to obtain a precursor powder; Step (4): Perform primary sintering treatment on the precursor powder to obtain a pre-sintered material; Step (5): Add a carbon source to the pre-sintered material and perform secondary sanding treatment to obtain a second abrasive; Step (6): After spray-drying the second abrasive, perform secondary sintering treatment to obtain the cathode material.

3. The high-compactness sodium iron pyrophosphate phosphate cathode material according to claim 2, characterized in that, In the said step (1), the iron source is lamellar iron phosphate, and the lamellar thickness of the lamellar iron phosphate < 200 nm; the particle size D50 of the lamellar iron phosphate < 15 μm.

4. The high-compaction sodium iron pyrophosphate phosphate cathode material according to claim 2, wherein In the said step (1), the sodium source is one or more of sodium carbonate, sodium oxalate, sodium pyrophosphate, sodium dihydrogen pyrophosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate; In the said step (1), the phosphorus source is one or more of sodium pyrophosphate, sodium dihydrogen pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; In the said step (1), the carbon source is one or more of glucose, sucrose, citric acid, ascorbic acid, and polyethylene glycol; In the said step (1), the vanadium source is one or more of vanadium carbonate, vanadium pentoxide, and ammonium metavanadate; In the said step (1), the titanium source is one or more of titanium dioxide, tetrabutyl titanate, and tetraisopropyl titanate; In the said step (1), the zirconium source is one or more of sodium zirconate, zirconium dioxide, and zirconium hydroxide.

5. The high-compactness sodium iron pyrophosphate phosphate cathode material according to claim 2, characterized in that, In the said step (1), the molar ratio of sodium, iron, and phosphorus elements is 4∶2.9∶4, and the carbon source accounts for 6%-10% of the total weight of the iron source; the molar doping amounts of V, Ti, and Zr are: 0.001 ≤ x ≤ 0.01, 0.002 ≤ y ≤ 0.01, 0.001 ≤ z ≤ 0.

01.

6. The high-compactness sodium iron pyrophosphate phosphate cathode material according to claim 2, wherein In the said step (2), the specific steps of the primary sanding treatment are: Place the mixed slurry in a sand mill, use zirconia beads with a diameter of 0.3-0.5 mm, sand at a rotation speed of 800 rpm for 4 h, and control the particle size distribution of the first abrasive D50 = 8 μm, D90 = 15 μm.

7. The high-compactness sodium iron pyrophosphate phosphate cathode material according to claim 2, wherein In the said step (3), the specific steps of spray granulation are: Transfer the first abrasive into a spray dryer and granulate under the conditions of an inlet air temperature of 200 °C and an atomization pressure of 3 bar to obtain a spherical precursor powder with a smooth surface and a particle size of 10-20 μm.

8. The high-compact sodium iron pyrophosphate phosphate cathode material according to claim 2, wherein, In the said step (4), the sintering regime for the primary sintering is: Heat from room temperature to 300 °C at a heating rate of 2 °C / min, keep it warm for 3 h in an N2 atmosphere, then heat up to 500 °C, and keep it warm for 12 h in a 5 wt% H2 / N2 reducing atmosphere.

9. The high-compactness sodium iron pyrophosphate phosphate cathode material according to claim 2, wherein In the said step (5), the carbon source accounts for 4%-8% of the total weight of the pre-sintered material; the sintering regime for the secondary sintering is: Heat from room temperature to 530 °C at a heating rate of 2 °C / min and keep it warm for 10 h in an N2 atmosphere.

10. A sodium-ion battery, comprising a positive electrode material, an electrolyte, a negative electrode material, and a separator, characterized in that, The cathode material is the high-compact sodium iron pyrophosphate cathode material described in claim 2.

Citation Information

Patent Citations

  • Wide-temperature sodium ion battery based on iron-based polyanionic positive electrode and carbon-based negative electrode

    CN114243005A

  • High-energy density type polyanion positive electrode material, preparation method thereof and sodium ion battery positive electrode plate

    CN117936755A

  • Carbon-coated ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN118213528A

  • Porous positive electrode material, preparation method thereof, positive electrode plate, secondary battery and electric equipment

    CN118431464A

  • Preparation method of high-compaction ferric sodium pyrophosphate positive electrode material and vehicle

    CN119349541A

Cited By

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and electrochemical device

    CN121134721A

  • Ferric sodium pyrophosphate phosphate positive electrode material and preparation method thereof, and electrochemical device

    CN121134721B

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN122267072A